2021
DOI: 10.1007/s00259-021-05350-y
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation study of targeted alpha therapy with [225Ac]Ac-DOTA-substance P in recurrence glioblastoma – safety and efficacy

Abstract: Glioblastoma is the most common and malignant primary brain tumour, with a poor prognosis. Introduction of new treatment options is critically important. The study aimed to assess the appropriateness of escalation doses and toxicity of [225Ac]Ac-DOTA-SP therapy. Material and methods A total of 21 patients (age of 43.0 ± 9.5 years), with histologically confirmed recurrent or conversion glioblastoma grade 4 following a standard therapy, have been included in the study. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…These peptides, conjugated with the macrocyclic chelators (DOTA or DOTAGA), were labelled with 90 Y, 177 Lu or 213 Bi. SP-based radioconjugates labelled with 225 Ac have also been subject to in vitro [11] and in vivo [8,12] investigations.…”
Section: Introductionmentioning
confidence: 99%
“…These peptides, conjugated with the macrocyclic chelators (DOTA or DOTAGA), were labelled with 90 Y, 177 Lu or 213 Bi. SP-based radioconjugates labelled with 225 Ac have also been subject to in vitro [11] and in vivo [8,12] investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Complex DNA damage significantly contributes to exceeding the cellular capabilities of DNA repair, thereby forcing cells towards cell death [ 20 ]. The first positive clinical trials on TAT have emerged, and TAT was suggested as a facilitator to overcome tumoral resistance to chemotherapy [ 47 , 48 ]. A nice example is the astatine-211 radiolabeled PARPi, which induced cellular lethality by targeting alpha-emitters directly to the nucleus, with high sensitivity in neuroblastoma in vitro and in vivo.…”
Section: Ddr (Radio)pharmaceuticalsmentioning
confidence: 99%
“…[14] [ 225 Ac][Ac(DOTA)]administered intravenously to adult C57BL/6 mice cleared rapidly via the urine, demonstrating that the complex is stable in vivo for at least 5 h. [14,40] Several constructs using [ 225 Ac] [Ac(DOTA)]have subsequently been produced featuring targeting groups, including small molecules, peptides, and antibodies. [21,[24][25][26][27][28][29][30][31]39,[41][42][43][44][45][46][47] Initial studies to prepare [ 225 Ac][AcDOTA] --antibody constructs utilised a two-step procedure that involved radiolabelling the bifunctional p-SCN-Bn-H 4 DOTA (Bn ¼ benzyl) chelator with 225 Ac 3þ at 55-608C before attachment to temperaturesensitive antibodies. [48] This process was utilised successfully to prepare the anti-prostate specific membrane antigen (PSMA) construct [ 225 Ac][Ac(DOTA-J591)] -, which was readily internalised by cancer cells and led to tumour regression and prolonged survival of mice bearing prostate carcinoma.…”
Section: Actinium-225 Chemistrymentioning
confidence: 99%